Le polycentrisme de l'aire métropolitaine de Paris : rhétorique de la planification territoriale ou organisation « métapolitaine » de l'espace ? - Philippe Thiard; Martine Berger (Territoire en Mouvement)
Polycentrism once was the corner stone of urban planning theory in Ile-de-France. 40 years after it was created and 30 years it was officially recognised by regional planning regulations, it has finally become a socio-economical reality. Urban and rural centers of the metropolitan area, in spite of urban sprawl, have concentrated economic as well as demographic growth for the last 20 years. Nevertheless, its consequence is an increased social division of housing and work within the most important metropolitan urban area of France.